Application of ETS-10 microporous titanosilicate as support of Ru nanoparticles for hydrogen production - Faroldi, Betina María Cecilia (2012)
Supported ruthenium catalysts have been shown to be effective for the dry reforming of methane.Besides, ETS-10 titanosilicate has properties able to disperse Ru species. In this work,  microporous ETS-10 titanosilicate was synthesized by hydrothermal synthesis employing anatase as Ti source. Ru was incorporated using three different methods: by incipient wetness impregnation (RuH), by ion exchange (RuI) and by adding Ru to the gel synthesis (RuG). The species present in the solids were characterized by XRD, N2 adsorption, ICP, SEM, TEM, EDX, TGA, TPR, UV?vis and XPS.RuH and RuI catalysts were found to be active and stable for the dry reforming of methane. These results show the potential application of ETS-10 as support of Ru catalysts for the production of hydrogen.